Sol–gel based portable optical sensor for simultaneous and minimal invasive measurement of pH and dissolved oxygen. (January 2015) - Deepa, N.; Balaji Ganesh, A.
Highlights: Minimal invasive and simultaneous measurement of pH and dissolved oxygen. Characteristics, response time, repeatability and reproducibility are evaluated. Results are compared with commercially available standard instruments. The portable sensor offers real-time analysis of both pH and dissolved oxygen. Measures the pH and dissolved oxygen in cuvette and transparent container. Abstract: The paper presents a hand-held optical sensor for simultaneous and minimal invasive measurement of pH and dissolved oxygen using sol–gel based sensing membranes which are attached internally in any see-through container. The sensing system shows the stable results over the period of time and possess the characteristics such as, minimum response time and repeatability. The disposable membranes are prepared using simple procedures and are very thin in size that can be attached the inner surfaces of transparent columns such as, measuring jar, conical flask, cuvettes and bio reactors. The pH sensor can be applied to the range between 3 pH and 9 pH, however, it shows good sensitivity between 4 pH and 9 pH with the response time of less than 10 s. The dissolved oxygen is measured in the range from 2 mg/L to 9 mg/L. It is found that, the opto electronic system posses the features, such as in-situ, simple, cost efficient, handheld and field deployable.